Modeling massage in the treatment of localized adiposity - Oliveira, Fernanda Tainara Lemes; Amorese, Roberta Chaves Penco (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 40 No especial (2024): Estética e Cosmética, 2024)
Currently, the media and society impose that we must have a perfect image without body imperfections, which justifies the increase in the demand for modeling massages in the world of aesthetics. Localized lipodystrophy consists of the accumulation of fats in certain regions of the body, which can be reduced through modeling massage, one of the existing procedures to treat this dysfunction. The present bibliographic study aims to describe the benefits that modeling massage brings in the treatment of localized adiposity analyzing the different methods used in the treatment aiming at improving self-esteem as well as the patient's quality of life.